On characterization of inextensible flows of tangent developable surfaces of timelike biharmonic general helices in the lorentzian E(1, 1) - Korpinar, Talat; Turhan, Essin (My University, 2013)
In this paper, we study inextensible flows of tangent developable surfaces of timelike biharmonic general helices in the Lorentzian group of rigid motions E(1, 1). We obtain the corresponding equations for the inextensible flow of tangent developable surfaces of timelike biharmonic general helices in the Lorentzian group of rigid motions E(1, 1). © 2013 by the Mathematical Association of Thailand. All rights reserved.
Keywords: Bienergy; Biharmonic curve; General helix; Geometric flows; Harmonic map